2021
DOI: 10.3390/ejihpe11030063
|View full text |Cite
|
Sign up to set email alerts
|

Association between Change in Regional Phase Angle and Jump Performance: A Pilot Study in Serie A Soccer Players

Abstract: Purpose: This observational longitudinal investigation aimed to investigate whether change in bioelectrical regional phase angle (PhA) is a predictor of change in vertical jump performance in elite soccer players. Methods: Fifteen soccer players (age: 28.7 ± 5.0 years, body weight: 82.4 ± 6.8 kg, height: 186.0 ± 0.1 cm, body mass index: 23.8 ± 1.2 kg/m2) competing in the first Italian division (Serie A) were included in this study and tested before the pre-season period and after the first half of the champion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 12 publications
4
25
1
1
Order By: Relevance
“…A large proportion of vertical jump- and sprint-performance variance can then be estimated solely from LPhA-related measures. Of note, this finding is in line with that observed by Bongiovanni and colleagues [ 21 ] in adult professional soccer players. The authors revealed that changes in LPhA were strongly related with changes in jump performance, explaining ~61% of the total variance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A large proportion of vertical jump- and sprint-performance variance can then be estimated solely from LPhA-related measures. Of note, this finding is in line with that observed by Bongiovanni and colleagues [ 21 ] in adult professional soccer players. The authors revealed that changes in LPhA were strongly related with changes in jump performance, explaining ~61% of the total variance.…”
Section: Discussionsupporting
confidence: 93%
“…While one study did not report any improvement when using regional measures of PhA to estimate lower-body power compared with WBPhA [ 16 ], regional BIA approaches have been proven effective in individual and team sports to monitor health, training-induced changes, and fitness level [ 23 , 42 ]. This is in accordance with the results of a previous study [ 21 ] showing the potential superior usefulness of LPhA, compared with WBPhA, as a surrogate marker of lower-body neuromuscular performance in elite soccer players.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Considering that soccer is characterized as an intermittent activity, with events changing every 3 to 5 s, it is well understood that players must be prepared for intense actions that include jumping, turning, tackling, high-speed running and sprinting [ 2 , 3 ]. In addition to the above, the social magnitude of soccer, together with a demanding and uncertain sporting and extra-sporting context, exposes the player to situations that he may perceive as a threat, perceiving depending on the individual anxiogenic characteristics (intensity), interpreting them as facilitators or enhancers of sporting performance (courage/direction).…”
Section: Introductionmentioning
confidence: 99%